ANALISIS PENGARUH DAYA TARIK WISATA TERHDAP MINAT BERKUNJUNG WISATAWAN DI PETAK SEMBILAN JAKARTA BARAT - Celina, Felicia; Sarudin, Rendy (Jurnal Ilmiah Global Education, 2023)
This study aims to determine the effect of tourist attraction on the interest of visiting tourists in Petak Sembilan, West Jakarta. This research was conducted using a quantitative approach and using a non-probability sampling technique with purposive sampling. Distribution was carried out to 100 respondents using a questionnaire. The population in this study focuses on respondents who know Petak Sembilan and have visited Petak Sembilan at least once. In this study, two variables were observed, namely Tourist Attraction as the independent variable and Interest in Visiting Tourists as the dependent variable. The research instruments were tested by validity and reliability tests, data analysis using simple linear regression, hypothesis testing using the coefficient of determination and data processing using SPSS version 25. In this study it was recognized that there are other factors that can also affect tourists' visiting intentions. Around 60.2% of the interest in visiting tourists can be explained by the variable tourist attraction.